2017
DOI: 10.26451/abc.04.03.11.2017
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized Eye Use Towards Video Stimuli in Bearded Dragons (Pogona vitticeps)

Abstract: Lateralized eye use is thought to increase brain efficiency, as the two hemispheres process different information perceived by the eyes. It has been observed in a wide variety of vertebrate species and, in general, information about conspecifics appear to elicit a left eye preference whilst information about prey elicits the opposite. In reptiles, this phenomenon has only been investigated using live conspecifics in agonistic contexts, and so it is not clear whether it can be found when using video stimuli. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…Other paradigms have been successful with free-ranging macaques [ 56 , 57 , 58 , 59 , 60 ]. Future research might also investigate neglected taxa, like recent studies measuring looking behaviour towards conspecific [ 61 ] and predator [ 62 ] stimuli in lizards.…”
Section: Literature Review: Results and Discussionmentioning
confidence: 99%
“…Other paradigms have been successful with free-ranging macaques [ 56 , 57 , 58 , 59 , 60 ]. Future research might also investigate neglected taxa, like recent studies measuring looking behaviour towards conspecific [ 61 ] and predator [ 62 ] stimuli in lizards.…”
Section: Literature Review: Results and Discussionmentioning
confidence: 99%
“…Previous research in bearded dragons using videos of live conspecifics showed that females exhibited a left eye bias towards conspecifics while males did not, and both sexes used their left eye significantly longer when viewing moving stimuli rather than stationary stimuli (Frohnwieser et al 2017). These stimuli were non-threatening, as all recorded animals were females and did not exhibit head bobbing.…”
Section: Ratio Of Left Eye Use To Right Eye Usementioning
confidence: 74%
“…We expected bearded dragons to show a greater relative left eye preference towards: (i) models of conspecifics than towards random objects; (ii) towards stimuli with eyes than without eyes; (iii) towards naturally colored models than towards gray ones; and (iv) towards moving than stationary robots. Furthermore, we expected females to show more lateralization towards conspecific stimuli than males, as was shown in a previous study using video stimuli (Frohnwieser et al 2017). Finally, we expected males to exhibit antagonistic behavior towards head bobbing robots, such as head bobbing themselves or approaching the stimulus.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…A computer monitor was positioned in one end of the arena, this was used to present video stimuli to the observer animal ( figure 1 a ). Bearded dragons have been shown previously to respond to videos of conspecifics [ 35 ].
Figure 1.
…”
Section: Methodsmentioning
confidence: 99%